Effectiveness of Yiqi Fumai lyophilized injection for acute heart failure: Rationale and design of the AUGUST-AHF cohort study - Zhang, Xuecheng; Kang, Jing; Zhang, Jingjing; Chen, Ying; Dai, Hengheng; Hu, Mingzhi; Liu, Yan; Shang, Hongcai (Frontiers in Cardiovascular Medicine, 2023)
Introduction The effect of Yiqi Fumai lyophilized injection (YQFM) on acute heart failure (AHF) patients has been evaluated in a large sample, randomized, controlled trial (AUGUST-AHF RCT study). However, restrictive eligibility criteria from a randomized clinical trial may raise concerns about the generalizability of the results to under-represented groups or complex patients with multimorbidity. Therefore, we intend to conduct the AUGUST-AHF cohort study which aims to assess the effectiveness of YQFM in patients with AHF in a real-world setting and compare the results with AUGUST-AHF RCT study. Methods and analysis This prospective, multicenter cohort study will be conducted at 50 secondary and tertiary hospitals in China and comprise 1,200 patients with AHF. The participants will be followed for up to at least 180 days. The primary outcome is a composite of 90-day all-cause mortality or readmission for heart failure. The secondary outcomes include length of hospital stay, cardiac-specific death, MACE, NYHA cardiac function classification. Cox proportional-hazards regression models will be used to estimate the association between YQFM use and the primary outcome. The primary analysis will use propensity-score matching methods to balance the differences in baseline variables between treatment cohorts. Ethics and dissemination Approval for the study has been obtained from the Ethical Committee of Dongzhimen Hospital (approval No. 2022DZMEC-327-02) and registered at ClinicalTrials.gov (NCT05586048). The study results will be published in peer-reviewed journals and presented at scientific conferences.